2016
DOI: 10.1063/1.4961606
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the interface characteristics of Y2O3/GaAs under biaxial strain, triaxial strain, and non-strain conditions

Abstract: We investigate the interface behaviors of Y2O3/GaAs under biaxial strain, triaxial strain, and non-strain conditions. This study is performed by first principles calculations based on density functional theory (DFT). First of all, the biaxial strain is realized by changing the lattice constants in ab plane. Averaged electrostatic potential (AEP) is aligned by establishing Y2O3 and GaAs (110) surfaces. The band offsets of Y2O3/GaAs interface under biaxial strain are investigated by generalized gradient approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 125 publications
1
6
0
Order By: Relevance
“…For MoS 2 surface, the planar AEP in the atomic region exhibits a periodic oscillation, while it remains constant in the vacuum region. 67 It is found that the shape of planar AEP do not change as the number of the MoS 2 layers changes from 1 to 6. For aAl 2 O 3 surface, the planar AEP in the atomic region has no obvious periodicity.…”
Section: Resultsmentioning
confidence: 87%
“…For MoS 2 surface, the planar AEP in the atomic region exhibits a periodic oscillation, while it remains constant in the vacuum region. 67 It is found that the shape of planar AEP do not change as the number of the MoS 2 layers changes from 1 to 6. For aAl 2 O 3 surface, the planar AEP in the atomic region has no obvious periodicity.…”
Section: Resultsmentioning
confidence: 87%
“…It is noted that the interface spacing affects the band offsets, resulting in deviation between theoretical calculation and experiment. [55][56][57][58] The layer electronic density of states for SrO/Ga(1) and HfO 2 /Ga(2) is presented in Fig.6. The chemical formula of symmetric slab is Hf 20 Sr 24 O 64 /Ga 36 As 32 for SrO/Ga (1) and Hf 24 Sr 20 O 68 /Ga 36 As 32 for HfO 2 /Ga(2).…”
Section: Resultsmentioning
confidence: 99%
“…It is noted that the interface spacing affects the band offsets, resulting in deviation between theoretical calculation and experiment. [55][56][57][58] The layer electronic density of states for SrO/Ga(1) and HfO 2 /Ga(2) is presented in Fig. 6.…”
Section: Resultsmentioning
confidence: 99%
“…The charge states of these defects are mainly determined by +1, -1, and The result shows that the defects act as carrier traps. In addition, charge defects also lead to region of fixed charge that can scatter carrier and shift the threshold voltage of the device [39].…”
Section: Stacking Orders Of A-a A-b A-c A-d A-e A-f and A-g Cmentioning
confidence: 99%